Reconstruction of Severely Atrophied Mandible and Simultaneous Implant Insertion with an Inverted Sandwich Technique - Milad Etemadi Sh; Alireza Tamizifar; Fatemeh Aghajani; Mahshad Saei (Hindawi Limited, 2023)
Objectives. To reconstruct and rehabilitate a severely atrophied mandible. Case presentation. A 40-year-old female patient with the chief complaint of denture instability was admitted to our care. In our opinion, the optimum reconstructive method for their severely atrophied mandible (width of 4 mm) was bone grafting with an inverted sandwich technique. 2 split-thickness autogenous calvarial grafts were attained. 4 onlay bone blocks were prepared, placed with an inverted sandwich technique, and fixed with 8 lag screws. 4 implants (Osstem, ⌀4×10 mm) were placed simultaneously, and an immediate post-operation cone beam computed tomography confirmed the proper placement of the grafts and implants. No complications were reported within 4 and 8 months following graft and implant placement. Final impressions for full dental rehabilitation were taken at the 8-month follow-up. Conclusion. Split-thickness calvarial grafts and simultaneous implant placement seem to be a very efficient and promising approach for major reconstruction of the mandible. However, further studies are recommended.